PENGEMBANGAN EKOWISATA KAWASAN KONVERSI HUTAN MANGROVE KALIMANTAN TIMUR - Arwin Sanjaya, Sarwo Eddi Wibowo (RJABM (Research Journal of Accounting and Business Management), 2019)
Ecotourism is a journey that has the purpose to conserve the environment and preserve the life and also the economic of the surrounding population around of the ecotourism. It is having the responsibility for the natural area also. Ecotourism can be seen as a concept of developing sustainable tourism, ecotourism purpose is to support environmental conservation efforts and can increase community participation in its management. Mangrove ecotourism is one of the popular ecotourism but has several problems. The problems are in its conservation activities itself. This study uses a qualitative descriptive approach and an interactive data analysis model. The results showed that the development of Ecotourism in the Mangrove Forest Conservation Area was carried out by local communities supported by the government, NGO, and the private sector through various programs that was helped by the  local communities to continue and to become more productive in preserving and maintaining the natural environment of the mangrove area to be better aims in the future. The policy and role of the institutions in the Developing of Ecotourism (Ekowisata) in Mangrove Forest Conservation Areas it could be hoped to improve and increase the living standard of local communities if it is managed properly and correctly. The role of institutions are to give many contributions and also for providing